IS AN INTERNATIONAL CORPORATE HUMAN RIGHTS LIABILITY FRAMEWORK NEEDED? AN ECONOMIC POWER, BUSINESS AND HUMAN RIGHTS, AND AMERICAN EXTRATERRITORIAL JURISDICTION ANALYSIS - Carlos Arevalo (Opinión Jurídica)
All companies, regardless of the sector they belong to, can positively or negatively impact human rights. Governments are increasingly aware of the benefits that free trade brings their nations, which has led them to do whatever is necessary to attract foreign investment, even if it means to act against the interests of their own people. The power relationship between corporations and states generates a tension derived from their nature: while the objective of states is the welfare of its members, the purpose of corporations is profit. It is in the crack generated by the collision of powers and purposes between these two actors, that this article is intended to raise the discussion on the need to establish an international framework for corporate liability for human rights violations. To achieve its goal, the article will analyze the opportunities and obstacles raised by the exercise of extraterritorial jurisdiction in the American context and its relationship with the developments in the business and human rights field.